The faces hidden in the anatomy of Michelangelo Buonarroti’s Pietà in the Vatican: The faces hidden in the Vatican’s Pietà - de Campos, Deivis; Buso, Luciano (Acta Biomedica Atenei Parmensis, 2021)
The study of human anatomy, besides being fundamental to the practice of medicine, has traditionally always been present in the daily life of many Renaissance artists. In this context, the specialized literature has described the famous Renaissance artist Michelangelo Buonarroti (1475-1564) as being among the greatest artist-anatomists of his time. Thus, many researchers have tried to better understand the inspirations of this famous artist, and even the possible diseases that affected this genius of human anatomy. Therefore, for the first time, this manuscript provides evidence that Michelangelo Buonarroti may have concealed letters, numbers, and faces in the anatomy of the Vatican’s Pietà [Virgin Mary/Jesus Christ] in 1498-9. The revelation of these findings, besides testifying to the artist’s considerable skill in representing the corporeal forms in his sculptures, will also be provide useful insights into the iconographic understanding of a work of art that is undoubtedly one of the most important of the Renaissance. Moreover, the present study shall be important for professionals in the medico-artistic field and those who keep some interest in the history of human anatomy, which is undoubtedly a fundamental discipline for the practice of medicine.